Assessing Burden of Under-Nutrition among Underfive Children of Urban Slum by Using Composite Index of Anthropometric Failure in Ahmedabad City, Gujarat, India - Swarna Rastogi; Chaitanya Maheshwari; Santosh Kr Raghav; M K Lala (Medsci Publications, 2017)
Introduction: Reduction in child malnutrition is another MDG related to an improvement in child welfare. National data on underweight provided under NFHS-4 (National Family Health Survey) (2015-16) revealed underweight prevalence rate around 35.8%. Objectives: To assess prevalence of under nutrition by composite index of anthropometric failure (CIAF) among under-five children of urban slums, Ahmedabad, Gujarat. Methods and Materials: It was a Cross-sectional study done among 121 under-fives at anganwadisof B.J. Medical College, Ahmedabad using simple random sampling. Their nutritional status was expressed in Z score for WAZ, [H (L) AZ], and [WH (L) Z] as per WHO international growth standards 2006. Result: Among 121 under-fives, the prevalence of underweight was 50%, whereas CIAF was 73.4%. Composite anthropometric index provides the actual prevalence or proportion of undernourished children in a community. So the policies should be based on the basis of Composite Index of Anthropometric Failure so to reduce the prevalence of under-nutrition in the community more effectively. Conclusion: Since CIAF is more than estimated by any of the three conventional indicators, it proves to be a better indicator in assessing the overall burden of under-nutrition in a population.